2022
DOI: 10.4250/jcvi.2021.0110
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Annulus Calcification and Cardiac Conduction Disturbances: A DANCAVAS Sub-study

Abstract: BACKGROUND Due to its location very close to the bundle of His, mitral annulus calcification (MAC) might be associated with the development of atrioventricular (AV) conduction disturbances. This study assessed the association between MAC and AV conduction disturbances identified by cardiac implantable electronic device (CIED) use and electrocardiographic parameters. The association between MAC and traditional cardiovascular risk factors was also assessed. METHODS This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The concept of MAC progression is generally accepted because MAC is a disease of degenerative nature. In fact, several studies have demonstrated the risk factors for MAC occurrence and their clinical significance regarding all‐cause mortality and stroke, 4 , 5 , 7 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Recently, Kato et al 22 , 23 also demonstrated that the prevalence of MAC was 23% in 24 414 patients. Patients with MAC had a higher risk of mortality, worse outcomes, and mitral valve dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of MAC progression is generally accepted because MAC is a disease of degenerative nature. In fact, several studies have demonstrated the risk factors for MAC occurrence and their clinical significance regarding all‐cause mortality and stroke, 4 , 5 , 7 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Recently, Kato et al 22 , 23 also demonstrated that the prevalence of MAC was 23% in 24 414 patients. Patients with MAC had a higher risk of mortality, worse outcomes, and mitral valve dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Affecting up to 24.1% of patients referred to surgical mitral regurgitation (MR) repair, 1 MAC is now regarded as a correlate of numerous disease processes, most of which share an increased atherosclerotic hazard. 2,3 Also, it has been linked to adverse valvular 4 and arrhythmic sequelae, 5,6 as well as to a more complex MV surgical course. 7 Currently, there are scarce data concerning the clinical implications of MAC extent in the ever-expanding mitral transcatheter edge-to-edge repair (TEER) population.…”
mentioning
confidence: 99%